New Data on Successful Invasion of Mediterranean Predatory Mite Typhlodromus beglarovi (Parasitiformes, Phytoseiidae) into the Forest-Steppe of Ukraine - Kolodochka, L.A.; L.A., I.D.Omeri (Вестник зоологии, 2010)
Evidences of more than 30 years (1975–2007) existence of the northern isolated population Forest-Steppe of Ukraine (near Kozyn Village, Obukhiv District, Kyiv Oblast, Ukraine) is given. It is considered as an example of unpremeditated introduction of a beneficial predating mite together with transported plants. This is the first registered and investigated case of invasion, acclimatization and inclusion biocoenosis as an equal right member for mites of the family Phytoseiidae. Обоснованное подтверждение 30-летнего (1975–2007 гг.) существования северной изолированной популяции средиземноморского вида Typhlodromus beglarovi Kuznetsov, 1984 в Лесостепи Украины (окр. с. Козин, Обуховский р-н, Киевская обл., Украина) как примера непреднамеренной интродукции полезного хищного клеща с завозными растениями. Для клещей семейства Phytoseiidae это первый исследованный случай инвазии, акклиматизации и вхождения в биоценоз в качестве равноправного члена сообщества.